2005
DOI: 10.1021/np040218p
|View full text |Cite
|
Sign up to set email alerts
|

Cucurbitane-Type Triterpenoids from the Fruit of Momordica charantia

Abstract: The structures of three new cucurbitane-type triterpenoids isolated from the methanol extract of the fruit of Japanese Momordica charantia were established as (19R,23E)-5beta,19-epoxy-19-methoxycucurbita-6,23,25-trien-3beta-ol (1), (23E)-3beta-hydroxy-7beta-methoxycucurbita-5,23,25-trien-19-al (2), and (23E)-3beta-hydroxy-7beta,25-dimethoxycucurbita-5,23-dien-19-al (3) on the basis of spectroscopic methods. These compounds were accompanied by the known (19R,23E)-5beta,19-epoxy-19,25-dimethoxycucurbita-6,23-die… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
50
0
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(52 citation statements)
references
References 12 publications
1
50
0
1
Order By: Relevance
“…The combined EtOAc soluble layer was subjected to repeated silica gel column chromatography and further purification by semi-preparative HPLC to yield compounds 1-9. The eight known compounds (2)(3)(4)(5)(6)(7)(8)(9) were identified by comparing their physical and spectral data with the reported values. The structure of the new sterol (1) was elucidated as follows.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The combined EtOAc soluble layer was subjected to repeated silica gel column chromatography and further purification by semi-preparative HPLC to yield compounds 1-9. The eight known compounds (2)(3)(4)(5)(6)(7)(8)(9) were identified by comparing their physical and spectral data with the reported values. The structure of the new sterol (1) was elucidated as follows.…”
Section: Resultsmentioning
confidence: 99%
“…Previous pharmacological studies have showed that the extracts or compounds of tissues of M. charantia possess anti-diabetic and anti-inflammatory activities. [1][2][3] Chemical investigations of M. charantia also revealed that more than seventy cucurbitane-type triterpenes have been isolated form the fruits, [3][4][5][6][7][8][9][10][11][12] seeds, 13,14 root, 15 and leaves and vines 16,17 of M. charantia. As part of our program aimed at the discovery of bioactive secondary metabolites from Taiwanese M. charantia, we had reported the isolation and structure elucidation of twenty-five cucurbitane-type triterpenoids from the MeOH extract of the stems of this plant.…”
Section: Introductionmentioning
confidence: 99%
“…The cucurbitane-type triterpenoids and their aglycones have shown some biological effects beneficial in treating diabetes and obesity, and possess anticancer, anti-HIV and antifeedant properties [7,39]. More than fifty cucurbitacins and cucurbitane glycosides from the fruits, seeds, leaves, vines and stems have been reported [40][41][42][43][44][45][46][47][48]. Recently, Chen et al (2008) isolated and structured elucidation of nineteen cucurbitacins named kuguacins A-E from the roots of MC [49] and kuguacins F-S [50] from the vines and leaves of MC.…”
Section: Phytochemicals and Cucurbitane Triterpenoidsmentioning
confidence: 99%
“…Recently, much phytochemical-research attention has focused on the metabolites and pharmacokinetics of saponins due to their biological activities and absorption profile (Akihisa et al, 2007;Donya et al, 2007;Harinantenaina et al, 2006;Kimura et al, 2005). Saponins are responsible for diverse effects including anti-inflammation, anti-allergy, antitumor, augmentation of the immune responses, stimulating the apoptosis of skin cells, anti-obesity and anti-hyperlipidemia (Awad et al, 2011;Amin et al, 2010;Wang et al, 2011).…”
Section: Introductionmentioning
confidence: 99%